Analysis of the Determinants of Economic Inequality in Bali Province - Cristalika Wulan; Anak Agung Ketut Ayuningsasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Economic inequality remains one of the major challenges faced by various regions, including Bali Province. This study aims to analyze the effects of GRDP per capita, investment, LFPR, minimum wage, tourist arrivals, and region on economic inequality in Bali Province, as well as to examine differences in economic inequality between the Sarbagita and non-Sarbagita regions. This research applies a quantitative approach with an associative research design. The study uses panel data regression combining cross-sectional and time-series data from nine regencies/cities in Bali Province during the period 2011–2024. The analytical method employed is panel data using the Random Effect Model (REM). The findings indicate that, simultaneously, GRDP per capita, investment, LFPR, minimum wage, tourist arrivals, and region significantly affect economic inequality in Bali Province. Partially, minimum wage and Labor Force Participation Rate (LFPR) have a negative and significant effect on economic inequality, while GRDP per capita, investment, and region have positive but insignificant effects. Number of tourist visits have a negative and insignificant effect on economic inequality. The implication of this study highlights the importance of more equitable investment distribution, expanded employment opportunities, improved human resource quality, and proportionate minimum wage policies in reducing economic inequality.